2017
DOI: 10.1136/jclinpath-2017-204815
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localisation of the stem cell markers OCT4, SOX2, NANOG, KLF4 and c-MYC in cancer: a review

Abstract: The stem cell markers octamer-binding transcription factor 4, sex-determining region Y-box 2, NANOG, Kruppel-like factor 4 and c-MYC are key factors in inducing pluripotency in somatic cells, and they have been used to detect cancer stem cell subpopulations in a range of cancer types. Recent literature has described the subcellular localisation of these markers and their potential implications on cellular function. This is a relatively complex and unexplored area of research, and the extent of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 52 publications
5
114
0
1
Order By: Relevance
“…It was reported that the stem cell associated genes, including OCT4, SOX-2 and Nanog and so on, have important roles in liver CSCs regulation. [25][26][27] As expected, miR-365 overexpression downregulated the expression of stemness-associated genes ( Figures 3A and 3B) and liver CSC markers in hepatoma cells ( Figures 3C and 3D), which further supported that miR-365 could inhibit liver CSCs expansion.…”
Section: Mir-365 Suppressed Liver Cscs Expansionsupporting
confidence: 82%
“…It was reported that the stem cell associated genes, including OCT4, SOX-2 and Nanog and so on, have important roles in liver CSCs regulation. [25][26][27] As expected, miR-365 overexpression downregulated the expression of stemness-associated genes ( Figures 3A and 3B) and liver CSC markers in hepatoma cells ( Figures 3C and 3D), which further supported that miR-365 could inhibit liver CSCs expansion.…”
Section: Mir-365 Suppressed Liver Cscs Expansionsupporting
confidence: 82%
“…KLF4, one of the well‐known Yamanaka factors, was the other increased protein in three SR HCC cell lines in this study. KLF4 plays pivotal roles in inducing the development of stem cells, inducing normal stem cells, pluripotent stem cells, and CSCs . CSCs are a small subpopulation of cancer cells with self‐renewal and pluripotency abilities.…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 plays pivotal roles in inducing the development of stem cells, inducing normal stem cells, pluripotent stem cells, and CSCs. 11 CSCs are a small subpopulation of cancer cells with self-renewal and pluripotency abilities. A growing number of studies suggest that CSCs are responsible for tumor development, recurrence and metastasis leading to tumor development, progression and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we examined the transcription factors Nanog and octamer‐binding transcription factor 4 (Oct4), which are usually expressed in embryonic stem cells, where they are involved in pluripotency regulation, proliferation and renewal. These transcription factors have also been used to detect cancer stem cell subpopulations (Iv Santaliz‐Ruiz et al ., ; van Schaijik et al ., ; Zheng et al ., ). The increased expression of all the genes analysed in sorafenib‐resistant cells (Fig.…”
Section: Resultsmentioning
confidence: 99%